Experimental investigation of exhaust thermal management on NOx emissions of heavy-duty diesel engine under the world Harmonized transient cycle (WHTC). (September 2018) - Bai, Shuzhan; Han, Jianlei; Liu, Min; Qin, Shunshun; Wang, Guihua; Li, Guo-xiang
Graphical abstract: The Figure shows the effect of the intake throttle valve on the NOx emission after SCR under the WHTC. The NOx emission decreased obviously with the intake throttle valve, the NOx emission values of cold start WHTC and hot start WHTC are reduced form 5.57 g/(kW·h) and 3.21 g/(kW·h) to 4.71g/(kW·h) and 1.64 g/(kW·h) respectively. The NOx emission weighting of the WHTC is reduced from 3.5 g/(kW·h) to 2.07 g/(kW·h), which is equivalent to a 41.5% reduction in NOx emissions. Highlights: The characteristics of exhaust temperature are investigated under cold start and hot start WHTC. The effects of intake throttle valve opening on NOx emission, fuel consumption, and urea consumption under WHTC were studied. The effects of DOC on the NOx conversion efficiency under WHTC were studied. Abstract: The control strategies of exhaust thermal management is experimental investigation to reduce Nitrogen oxides (NOx) emission under the world Harmonized transit cycle (WHTC) in this paper. The exhaust temperature of the 59.3% working conditions is lower than 200 °C under the cold start WHTC, and the average temperature of which is 196 °C, the urea injection system is in the state of stopping in most of time under cold start WHTC. The effects of intake throttle valve opening on NOx emission, fuel and urea consumption were studied in steady conditions with medium and low load. The 15–20% opening of intake throttle valve could increase the exhaust temperature to more than 200 °C when the torque is less than 250 N·m. The NOx emission weighted value of the WHTC is reduced by 41.5%, which could meet the requirements of the Europe V emission regulations for WHTC test cycle, but the fuel economy increase slightly. The Diesel Oxidation Catalyst (DOC) could increase the NO2 /NOx ratio in the exhaust gas effectively, and increase the NOx conversion efficiency in the temperature range of 200–400 °C, which reduce the NOx emission weighted value of the diesel engine under WHTC by 8.7%.